E-MODULE DISCOVERY MATERI IMPULS DAN MOMENTUM UNTUK MENGEMBANGKAN BERPIKIR TINGKAT TINGGI - Setiasiwi, Nafisah Irfani; Nugroho, Sunyoto Eko (UPEJ Unnes Physics Education Journal, 2023)
High-order thinking is one of the abilities needed in this era and the Indonesian government has been trying to develop it through the implementation of the curriculum in Indonesia. In its implementation, there are still several obstacles, one of which is the lack of supporting teaching materials and the use of technology that is less than optimal. The aim of this research is to develop an e-module discovery of impulses and momentum that is appropriate for developing students' higher order thinking. This study uses the 4D development model, up to the develop stage. The test subjects in this study were students of class XI MIPA 3 and XI MIPA 8 at SMA Negeri 1 Kendal. The e-module eligibility results are included in the feasible category in the material aspect with a score of 84% and the very feasible category in the media aspect with a score of 89%. The e-module readability test shows that the e-module is easy to understand with a score of 91.25%. The results of student responses are in the very good category with a score of 91.58%. The high-level thinking profile of students after using the e-module obtained a very good category with a score of 98 on the analyzing (C4) indicator, a very good category with a score of 93 on the evaluating (C5), and a good category with a score of 80 on the creative (C6) indicator.